CGRP and the Calcitonin Receptor are Co-Expressed in Mouse, Rat and Human Trigeminal Ganglia Neurons - Rees, Tayla A.; Russo, Andrew F.; O’Carroll, Simon J.; Hay, Debbie L.; Walker, Christopher S. (Frontiers in Physiology, 2022)
The neuropeptide calcitonin-gene related peptide (CGRP) is expressed in the trigeminal ganglia, a key site in craniofacial pain and migraine. CGRP potently activates two receptors: the CGRP receptor and the AMY1 receptor. These receptors are heterodimers consisting of receptor activity-modifying protein 1 (RAMP1) with either the calcitonin receptor-like receptor (CLR) to form the CGRP receptor or the calcitonin receptor (CTR) to form the AMY1 receptor. The expression of the CGRP receptor in trigeminal ganglia has been described in several studies; however, there is comparatively limited data available describing AMY1 receptor expression and in which cellular subtypes it is found. This research aimed to determine the relative distributions of the AMY1 receptor subunit, CTR, and CGRP in neurons or glia in rat, mouse and human trigeminal ganglia. Antibodies against CTR, CGRP and neuronal/glial cell markers were applied to trigeminal ganglia sections to investigate their distribution. CTR-like and CGRP-like immunoreactivity was observed in both discrete and overlapping populations of neurons. The data suggest that CTR and CGRP were primarily colocalized in C-fiber neurons, with only limited colocalization in A-fiber neurons. Staining was not typically observed in glial cells. Western blotting also identified CTR expression in the trigeminal ganglia of all three species. These results confirm that CTR is expressed in trigeminal ganglia neurons. The identification of populations of neurons that express both CGRP and CTR suggests that CGRP could act in an autocrine manner through a CTR-based receptor, such as the AMY1 receptor. Overall, this suggests that a trigeminal ganglia AMY1 receptor may be activated during migraine and could therefore represent a potential target to develop treatments for craniofacial pain and migraine.